Lithium-ion supercapacitors : fundamentals and energy applications - Zhang, Lei (Chemist); Wilkinson, David P.; Chen, Zhongwei (Professor); Zhang, Jiujun (Electrochemical energy storage and conversion (CRC Press), 2018)
The book provides a comprehensive understanding of the principles for operating lithium-ion supercapacitors, their challenges, technological trends and perspectives. This LISC technology has high potential to replace conventional main rechargeable batteries such as lead-acid and nickel metal hydride batteries for automotive, portable electronics, and stationary applications. The book offers detailed analysis of LISCs at the material, component, and system levels to evaluate the different approaches to their integration. It also discusses economics, market, manufacture, and commercialization status of LISCs--